2018
DOI: 10.1186/s12944-018-0766-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative modifications of foetal LDL-c and HDL-c lipoproteins in preeclampsia

Abstract: BackgroundOxidative modifications have been observed in lipids and proteins in lipoproteins isolated from women with preeclampsia. Thus, newborns could also be susceptible to this damage directly through their mothers. In this study, we evaluated the oxidative profile of LDL-c and HDL-c lipoproteins isolated from the umbilical cord from newborns born to women with preeclampsia.MethodsThirty newborns born to women with preeclampsia and thirty newborns born to women with healthy pregnancies were included. Lipid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…We observed that total cholesterol, as well as non-HDL-C, were profoundly increased in neonates of early-onset PE, while triglyceride levels and HDL-C were unaltered. These results of lipid measurements in PE cord blood are in line with a previous study [ 81 ]. However, it has to be noted that in our study, these changes were only seen in early-onset PE, which represents the more severe type.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that total cholesterol, as well as non-HDL-C, were profoundly increased in neonates of early-onset PE, while triglyceride levels and HDL-C were unaltered. These results of lipid measurements in PE cord blood are in line with a previous study [ 81 ]. However, it has to be noted that in our study, these changes were only seen in early-onset PE, which represents the more severe type.…”
Section: Discussionsupporting
confidence: 93%
“…Of particular interest, the PE-associated oxidative modifications of lipids in HDL and LDL were also found in fetal lipoproteins, showing that also the infants are affected by increased oxidative stress and clear transplacental transmission of these effects in PE [ 182 ]. Similar to the results in PE mothers [ 177 ], PON1 activity was also shown to be decreased in the cord blood of the newborns [ 182 ]. In another study, HDL isolated from cord blood of PE pregnancies was reported to be linked with significantly reduced levels of apoM [ 138 ].…”
Section: Pregnancy-related Diseases Affects Hdl Metabolism and Functionmentioning
confidence: 99%
“…This highly supported our findings that increased levels of anti-angiogenic sFLT1 resulted in early maternal metabolic changes, also influencing fetal metabolism [ 15 ]. As reviewed in [ 38 ], neonates born from PE mothers showed increased levels of lipoproteins and also oxidative damage in lipoproteins [ 39 ].…”
Section: Discussionmentioning
confidence: 99%